Curso pré-vestibular - Marchetti, Guilherme de Abreu [UNESP]; Proença, Letícia [UNESP]; Lopes, Maria Denise [UNESP]; Curvelo, Eliana [UNESP]; Prestes, Nereu Carlos [UNESP]; Rocha, Noeme Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The preparatory course for entrance exams it’s a type of education that prepares the students to join the Brazilian universities, either public or private ones. Therefore, the FMVZ, Botucatu campus, created a preparatory course for entrance exams to help students in disadvantage, either social or economic, to join the university in a fair way, so they can keep up with the college, without difficulty. Today, the course counts with 70 students of public high school, some form to play the role of the University on the support against the social inequality, through the education.

O curso pré-vestibular é a modalidade de ensino que prepara estudantes a ingressarem nas Universidades brasileiras, sejam elas públicas ou privadas. Assim, a FMVZ, campus de Botucatu, criou um curso pré-vestibular para auxiliar alunos em desvantagem, seja social ou econômica, a ingressarem na universidade de maneira justa, para que possam acompanhar o curso escolhido sem maiores dificuldades. Hoje, o curso conta com 70 alunos de ensino público, uma forma de exercer o papel da Faculdade no auxílio contra a desigualdade social, através educação.
Keywords: Tutoring; High school; Education; Reforço escolar; Ensino médico; Educação